Gastroduodenal mucosal defense mechanisms. Issue 6 (November 2015) - Said, Hyder; Kaji, Izumi; Kaunitz, Jonathan D.
Abstract : Purpose of review: To highlight recent developments in the field of gastroduodenal mucosal defense with emphasis on lumen–gut interactions. Recent findings: There has been a growing interest in the physiological functions of luminal chemosensors present from tongue to colon that detect organic molecules in the luminal content associated with nutrient ingestion, usually associated with specialized cells, in particular the enteroendocrine cells. These receptors transduce the release of peptide hormones, in particular proglucagon-derived products such as the glucagon-like peptides (GLPs), which have profound effects on gut function and on metabolism. Luminal chemosensors transduce GLP release in response to changes in the cellular environment, as part of the mechanism of nutrient chemosensing. GLP-2 has important trophic effects on the intestinal mucosa, including increasing the proliferation rate of stem cells and reducing transmucosal permeability to ions and small molecules, in addition to increasing the rate of duodenal bicarbonate secretion. GLP-1, although traditionally considered an incretin that enhances the effect of insulin on peripheral tissues, also has trophic effects on the intestinal epithelium. Summary: A better understanding of the mechanisms that mediate GLP release can further illuminate the importance of nutrient chemosensing as an important component of the mechanism that mediates the trophic effects of luminal nutrients. GLP-1 and GLP-2 are already in clinical use for the treatment of diabetes and intestinal failure. Improved understanding of the control of their release and their end-organ effects will identify new clinical indications and interventions that enhance their release.